She's the man [videorecording (DVD)] - Bynes, Amanda, 1986-; Tatum, Channing; Ramsey, Laura, 1982-; Hoffman, Robert, 1980-; Shakespeare, William, 1564-1616 (Paramount Pictures, 2017)
Complications arise in love and life when Viola pretends to be her brother after he ditches his elite boarding school to go on a London vacation.